Unfolding the Triplet Transition from Products to Complex Sustainable Solutions - Shahzad, Jahanzaib; Rabetino, Rodrigo (Palgrave Macmillan, 2026)
At the sweet spot of servitization, digitalization, and sustainability literature, this chapter explores sustainable servitization as a triplet transition of manufacturers toward providing complex sustainable solutions. The chapter presents a framework to navigate the transition’s complexity when manufacturers move from selling products and add-on services to delivering complex, environmentally friendly, and digitally enabled offerings. While digitalization is an enabler that impacts servitization strategies and drives service innovation, sustainability adds complexity, pushing companies to integrate environmental, social, and economic considerations into their operations and offerings. Thus, business model innovation is essential for this transition, as it redefines value creation, delivery, and capture to meet sustainability goals. The triple transition is challenging but can ultimately enhance competitiveness while supporting long-term sustainability goals.
Keywords: servitization; sustainability; solutions; produc-service systems; fi=Strateginen johtaminen|en=Strategic Management|; fi=Strateginen johtaminen|en=Strategic Management|